2022
DOI: 10.3389/fmed.2022.813367
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stigma and Self-Efficacy of Patients With Inflammatory Bowel Disease-Related Stoma in China: A Cross-Sectional Study

Abstract: BackgroundPatients with inflammatory bowel disease (IBD)-related stoma face physical, psychological, and social adjustment challenges. However, knowledge about stigmatization and self-management, which is important for clinical care and patient education strategies, is lacking.ObjectiveTo evaluate the level of stigma and self-management ability of Chinese patients with IBD-related stoma using an online questionnaire.MethodsParticipants were recruited from two general hospitals in mainland China and the interne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…In parallel with this study, it has been shown in the literature that social support has positive effects on stoma adaptation [ 23 , 34 ]. Wang et al showed that as the duration of stoma increases, self-efficacy increases, but self-efficacy levels decrease again in patients with a stoma longer than 5 years [ 35 ]. The time elapsed since stoma formation may have a positive effect on ostomy adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In parallel with this study, it has been shown in the literature that social support has positive effects on stoma adaptation [ 23 , 34 ]. Wang et al showed that as the duration of stoma increases, self-efficacy increases, but self-efficacy levels decrease again in patients with a stoma longer than 5 years [ 35 ]. The time elapsed since stoma formation may have a positive effect on ostomy adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…While self-efficacy is described as an individual’s belief in his or her very self, it is a factor that determines to start positive health behaviors and resume them, and it is a feature that determines how an individual will feel, think and behave [ 16 ]. In the literature, there are not only similar studies that show the stoma adaptation level to be medium [ 22 , 34 ] but also studies that found the self-effectiveness level to be over average [ 19 , 20 , 35 ]. In this study, the self-efficacy level was determined to be at a medium level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research population consisted of people with stoma who applied to the stoma and wound care unit of the hospital. The research sample consisted of volunteers aged between 18 and 65 with permanent stoma, who were not actively receiving any surgical treatment or chemotherapy or radiotherapy and who were sexually active. Individuals who were on antidepressants or sedatives and diagnosed by physician with a psychiatric disease and/ or sexual dysfunction and those receiving/continuing treatment for these diagnoses were excluded from the research.…”
Section: Participantsmentioning
confidence: 99%
“…If self-efficacy levels of individuals are high, they become active and exert more effort to deal with a situation [17]. For these reasons the self-efficacy of stoma patients is key to their adaptation to a new life and their psychological well-being [18] and may also affect sexuality, a component of psychological well-being. No study has been found in the literature that analyses the relationship between stoma self-efficacy and sexual life.…”
mentioning
confidence: 99%